Productivity Convergence in OECD Manufacturing Industries - Martin A. Carree; Luuk Klomp; A. Roy Thurik (Tinbergen Institute, 1999)
The extent of beta- and sigma-convergence of average labor productivity across manufacturing industries in 18 OECD-countries over the period 1972-1992 show large inter-industry differences. One reason for these differences is knowledge and capital barriers preventing catch-up to occur. We find the level of averagelabor productivity, as a proxy for these barriers, to be correlated with the extent of convergence.
Keywords: 330; Produktivität; OECD-Staaten